The Novel Mechanisms Concerning the Inhibitions of Palmitate-Induced Proinflammatory Factor Releases and Endogenous Cellular Stress with Astaxanthin on MIN6 β-Cells - Atsuko Kitahara; Kazuto Takahashi; Naru Morita; Toshitaka Murashima; Hirohisa Onuma; Yoshikazu Sumitani; Toshiaki Tanaka; Takuma Kondo; Toshio Hosaka; Hitoshi Ishida (Marine Drugs, 2017)
Astaxanthin, an antioxidant agent, can protect pancreatic β-cells of db/db mice from glucotoxicity and resolve chronic inflammation in adipose tissue. Nonetheless, the effects of astaxanthin on free-fatty-acid-induced inflammation and cellular stress in β-cells remain to be demonstrated. Meanwhile, palmitate enhances the secretion of pro-inflammatory adipokines monocyte chemoattractant protein-1 (MCP-1) and vascular endothelial growth factor (VEGF120). We therefore investigated the influence of astaxanthin on palmitate-stimulated MCP-1 and VEGF120 secretion in mouse insulinoma (MIN6) pancreatic β-cells. Furthermore, whether astaxanthin prevents cellular stress in MIN6 cells was also assessed. Pre-treatment with astaxanthin or with N-acetyl-cysteine (NAC) which is an antioxidant drug, significantly attenuated the palmitate-induced MCP-1 release through downregulation of phosphorylated c-Jun NH2-terminal protein kinase (JNK) pathways, and suppressed VEGF120 through the PI3K/Akt pathways relative to the cells stimulated with palmitate alone. In addition, palmitate significantly upregulated homologous protein (CHOP) and anti-glucose-regulated protein (GRP78), which are endoplasmic reticulum (ER) stress markers, in MIN6 cells. On the other hand, astaxanthin attenuated the increased CHOP content, but further up-regulated palmitate-stimulated GRP78 protein expression. By contrast, NAC had no effects on either CHOP or GRP78 enhancement induced by palmitate in MIN6 cells. In conclusion, astaxanthin diminishes the palmitate-stimulated increase in MCP-1 secretion via the downregulation of JNK pathways in MIN6 cells, and affects VEGF120 secretion through PI3K/Akt pathways. Moreover, astaxanthin can prevent not only oxidative stress caused endogenously by palmitate but also ER stress, which NAC fails to attenuate, via upregulation of GRP78, an ER chaperon.